Strategi Teknologi dan Kebijakan untuk Menjamin Privasi Data Pengguna dalam Perpustakaan Digital Era Modern - Persadha, Pratama Dahlian; Judijanto, Loso; Susanti, Melly; Reza, Heru Kreshna (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Security is becoming a very important element in the digital age, especially in the management and protection of information. With the increasing volume of information being processed, the need for adequate knowledge management and security provision is becoming more pressing. This research highlights the importance of cybersecurity in the context of digital libraries that must comply with certain technological standards and regulations to protect user data and ensure privacy when accessing electronic resources. Libraries face various challenges in protecting personal data on their electronic resources. This research explores topics such as user privacy, data encryption, access management, and compliance with privacy laws. By addressing these issues thoroughly, libraries can ensure the protection of user privacy while optimizing the benefits of digital resources in today's information environment. The October 2023 cyberattack by the hacker group Rhysida on the British Library's information systems underscores the importance of cybersecurity and data privacy for digital libraries. This research aims to provide insights and solutions to these challenges, so that digital libraries can operate securely and efficiently.